Materializing Borders and Learning to Think in Limits in 17th-century France - Rossman, Sasha (Artium Quaestiones, 2024)
A pietra dura table manufactured at the royal Gobelins workshops (Paris) in 1684 will serve as a case study for considering the historical dimensions of borders and how they take particular aesthetic forms. The table pictures a map of France, made out of a mosaic of differently colored pieces of marble. The map is traversed by representations of boundaries, between provinces and states as well as a five-part bounded frame that encircles the map. In this object, borders appear as both a lens through which one can learn about the world and control it, while simultaneously presenting boundaries as an embedded part of the material world: a delimited France as a figure that is also a (stone) ground. Considered in its historical dimension, however, the term “border” is insufficient for explaining the types of changes (political, scientific, and cultural) that produced this object. Indeed, during this period, the nature and vocabulary of borders was developing in new ways, just as the image of the state was slowly transitioning from a subject-based (monarchical) to a territorial-based concept of statehood. I argue that by examining the materiality of this particular table, as well as comparing it to other products of material culture from the period (including cartographic atlases and pedagogical lessons), we can recall how borders signified and assumed a particular form at a given historical moment. I propose that, in this context, borders took on specific visual and material forms that aimed to facilitate a kind of collaborative practice of understanding the world, and one’s place in it, in terms of bounded perimeters. The aim of reproducing this historical moment in border production is to encourage us to examine the historical determinants of borders today, both in their epistemological and aesthetic dimensions.